ANALISIS TANDA DALAM FILM SHAZAM! KARYA DAVID SANDBERG SUATU ANALISIS SEMIOTIK - Wowor, Juan Joshua; Rambing, Rosalina; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT       This research entitles “Sign Analysis in the movie Shazam! by David Sandberg. The aims of this research are to identify and classify the types of signs as well as to analyze the meaning of signs used in Shazam! movie. The writer uses the theory of Pierce (1955) in the process of identifying, classifying, and analyzing each scene containing the signs used the representament aspect. The method used in this study is descriptive method. To finish this study, the writer read some concepts related to the title about sign analysis and also downloaded resources from the internet. In collecting the data, the writer has watched 14 times Shazam! movie which is the object of the research. In addition to watching, the writer took pieces of image or visuals (screenshoot) from the movie scenes that are needed for research. The result of this research shows that based on the theory of Pierce there were 27 scenes in Shazam! movie, all of these scenes focus on Billy’s life and his family and in the 27 scenes there are 11 icons, 13 index, and 4 symbols. each sign had a different meanings._______________________________Keywords: Sign Analysis, Shazam! Movie, Descriptive Method, Semiotics Analysis.